Plasma Analyzer for the Chinese FY-3E Satellite: In-Orbit Performance and Ground Calibration - Xinyue Wang; Xiaoxin Zhang; Jinhua Wang; Cong Huang; Jiawei Li; Aibing Zhang; Linggao Kong; Dan Du; Yong Yang; Pengfei Zhang; Bin Su; Bin Liu; et al. (Atmosphere, 2023)
The plasma analyzer (PMA) on the Fengyun-3E (FY-3E) meteorological satellite series is a critical sensor of the space environment monitoring package that is capable of the comprehensive in situ detection of the thermal plasma environment and surface discharge effects. In this paper, we conducted a thorough evaluation of the PMA’s performance and reliability through a combination of ground-based laboratory calibration and in-orbit testing. During the ground-based calibration, the PMA underwent assessments for the energy range, field of view (FOV), and measurement accuracy, and obtained the detection accuracy and the geometric factors. During the in-orbit testing, the PMA successfully obtained the typical distribution characteristics of low-energy ions and electrons in orbital space regions, as well as the precipitating particles in the middle and high latitudes of both hemispheres. Notably, the PMA observed an expansion of the particle distribution in the high-latitude regions during a moderate geomagnetic storm. The results from both the ground-based calibration and in-orbit testing demonstrated that the PMA met the requirements for thermal plasma detection, with reliable and scientifically valid in-orbit detection data. These results provide a crucial foundation for studying spatial weather variations, improving the accuracy of space environment forecasts and enhancing disaster detection and monitoring capabilities.